Hip and groin injuries in professional basketball players: Impact on playing career and quality of life after retirement - Ekhtiari, S.; Khan, M.; Burrus, T.; Madden, K.; Gagnier, J.; Rogowski, J. P.; Maerz, T.; Bedi, A. (Sports Health: A Multidisciplinary Approach, 2019)
Background: Professional basketball players are at increased risk of hip and groin pain. Epidemiologic data exist on the prevalence of hip and groin issues among players in the National Basketball Association (NBA), but little is known about how these injuries affect athletes after retirement.